Geographical isolation and environmental heterogeneity contribute to the spatial genetic patterns of Quercus kerrii (Fagaceae). (March 2018) - Jiang, Xiao-Long; An, Miao; Zheng, Si-Si; Deng, Min; Su, Zhi-Hao
Abstract Southwest China is one of the major global biodiversity hotspots. The Tanaka line, extending within southwestern China from its northwest to its southeast, is an important biogeographical boundary between the Sino-Japanese and Sino-Himalayan floristic regions. Understanding the evolutionary history of the regional keystone species would assist with both reconstructing historical vegetation dynamics and ongoing biodiversity management. In this research, we combined phylogeographic methodologies and species distribution models (SDMs) to investigate the spatial genetic patterns and distribution dynamics ofQuercus kerrii, a dominant evergreen oak inhabiting southwest China lowland evergreen-broadleaved forests (EBLFs). A total of 403 individuals were sampled from 44 populations throughout southwest China. SDMs and mismatch distribution analysis indicated thatQ. kerrii has undergone northward expansion since the Last Glacial Maximum (LGM). Quantitative analysis revealed that the range expansion ofQ. kerrii since the LGM exceeded that of the sympatric mid-elevation speciesQuercus schottkyana, likely owing to their contrasting distribution elevations and habitat availabilities. The historical climate change since the LGM and the latitude gradient of the region played an important role in shaping the genetic diversity ofQ. kerrii . The genetic differentiation index and genetic distance surface ofQ. kerrii populations east of the Tanaka line exceeded those to its west. The long-term geographic isolation and environmental heterogeneity between the two sides of the Tanaka line might increase species divergence patterns and local adaptation. This study provides new insights into the historical dynamics of subtropical EBLFs and the changing biota of southwest China.